Obesity epidemic and the environment Latin America and the Caribbean region - Koengkan, Matheus; Fuinhas, Jose Alberto; Tavares, Aida Isabel P.; Silva, Nuno (Academic Press, 2022)
Obesity Epidemic and the Environment: Latin America and the Caribbean Region provides a broad analysis of the macroeconomic impact of the obesity epidemic on environmental degradation in the LAC region. Case studies combine theory and practice to achieve critical conclusions (and subsequent policy implications), providing useful tools for those working on actual health, energy and environmental challenges. Written for researchers, policymakers, international organizations and practitioners in various fields, especially those in public health, health economics, energy and environmental economics and social sciences, this book thoroughly highlights the obesity epidemic in this region. In the LAC region, obesity has become a public health issue. The increase of this problem is related to the economic gains obtained from the process of liberalization and privatization, the increase of foreign investment, and infrastructure investments.